Improving Student Mathematics Learning Outcomes Through the Implementation of PBL Models for Students of Class VII H SMPN 23 Pekanbaru - Suci Dwi Ananda; Erni Liana (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This classroom action research aims to improve student's learning process and outcomes by applying problem-based learning models in the class. The subjects of this study were 39 class VII H students of SMP Negeri 23 Pekanbaru with different levels of academic ability. This research was divided into 2 cycles, each consisting of four stages: planning, implementing, observing, and reflecting. The data collected was obtained from researchers' observations of the learning activities of teachers and students during class and learning outcomes tests in the form of daily tests. The results obtained are an increase in a better direction. This can be seen in students who participate actively and are more responsible in the learning process, such as discussing, presenting, expressing opinions, and asking questions to provide learning conclusions. The number of students who achieved KKM on the basic value, daily test I (cycle 1), and daily test II (cycle II) was 51.2%, 58.9%, and 66.7%. KKM presentations that experienced an increase from before to after the action showed that student learning outcomes improved. The results of this study indicate that the learning process using a problem-based learning model can improve the quality of learning and learning outcomes of class VII H students of SMP Negeri 23 Pekanbaru.